Beyond the Pet-Effect—Examining Bio-Psychosocial Aspects of Pet Ownership and Introducing the “Aunty Phenomenon” - Christine Smetaczek; Birgit Ursula Stetina (Pets)
Human–animal relationships have long been idealized as universally positive, but recent studies highlight the complexities and contradictions inherent in this bond. This study re-analyzes previously published data to examine the nuanced effects of pet ownership on human well-being, particularly under stressful circumstances such as the COVID-19 pandemic. Using a mixed-methods approach, data from three independent surveys (n = 840) were re-analyzed to explore the bio-psychosocial implications of pet companionship. Key instruments included the Quality of Life Questionnaire (WHOQOL-BREF), Beck Depression Inventory (BDI-II), and Lexington Attachment to Pets Scale (LAPS). Results revealed that pet ownership was significantly associated with higher levels of psychosocial stress, challenging the assumption that pets universally improve quality of life. Notably, individuals with current pet ownership reported lower quality of life compared to non-owners. However, qualitative analyses illustrated perceived emotional and social support among pet owners, reflecting the “pet-effect paradox.” Mental health variables such as depression and loneliness emerged as stronger predictors of well-being than pet attachment. This study introduces the “Aunty Phenomenon” as a conceptual framework to describe the idealization of pet relationships, while acknowledging the responsibilities they entail. These findings underscore the importance of a holistic approach to human–animal bond research.